Factors related to self-care in diabetes mellitus patients attended at Emergency Service in Mexico - Baquedano, Irasema Romero; Santos, Manoel Antônio dos; Teixeira, Carla Regina de Souza; Martins, Tatiane Aparecida; Zanetti, Maria Lúcia (Revista da Escola de Enfermagem da USP, 2010)
This cross-sectional study aimed to determine the self-care ability of individuals with type 2 diabetes mellitus and to relate this capacity with some sociodemographic and clinical variables. Participants were 251 patients who attended the Emergency Service at the Mérida Regional Hospital in Yucatán, Mexico, in 2006. Data were obtained through directed home interviews, using a form, a questionnaire and the Self-Care Capacity Scale. Descriptive and correlation statistics were used for data analysis. The results showed 83 (33.5%) subjects with good and 168 (66.5%) subjects with regular ability. A directly proportional correlation was found between self-care ability and years of study (r=0.124; p